Influence of Cation Nature on Stabilization of Gold Nanospecies in Mordenites; Journal of Nanoscience and Nanotechnology; Vol. 11, № 6 - Tuzovskaya I.; Lima E.; Bosch P.; Bogdanchikova N.; Pestryakov A. N. Aleksey Nikolaevich; Fraissard J. (2011, 2011)
Gold species deposited on NH+4- and H+-mordenites were studied by X-ray diffraction, xenon adsorption, NMR of 27Al and 129Xe, UV-Visible spectroscopy and TPR. Mordenite ion-exchange cations exert a significant effect on size distribution and electronic state of gold species supported on the zeolites. AuNH4M contains larger nanoparticles of gold on its external surface than AuHM because protonic form of zeolite has stronger sites for stabilization of gold nanospecies. In the case of NH+4-mordenite, Au clusters inside zeolite channels have bigger size and fill the side-pockets com- pletely after gold deposition due to more complete reduction of gold entities, while in H+-mordenite only half the side-pockets are filled by gold species. H+-mordenite favors the stabilization of both small gold clusters and cations. Even after the reduction of gold by hydrogen flow at 100 °C, some gold species are not completely reduced and have certain effective charge (Auδ+n clusters).